2013
DOI: 10.1007/s00038-013-0497-7
|View full text |Cite
|
Sign up to set email alerts
|

Health inequalities and regional specific scarcity in primary care physicians: ethical issues and criteria

Abstract: The discussion provides clear criteria for decision makers to consider when addressing primary care physician shortages. Yet, decision makers will still need to assess specific situations by these criteria to ensure that any decisions they make are morally justifiable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…that can significantly complicate their resolution ( 3 ). For example, how does one balance the free movement of health care professionals against maintaining the effective provision of regional health care ( 22 )? Scientific progress has also complicated issues by enhancing our understanding of the etiology of health states.…”
Section: Ethical Conflicts: a Review Of Ethical Topicsmentioning
confidence: 99%
“…that can significantly complicate their resolution ( 3 ). For example, how does one balance the free movement of health care professionals against maintaining the effective provision of regional health care ( 22 )? Scientific progress has also complicated issues by enhancing our understanding of the etiology of health states.…”
Section: Ethical Conflicts: a Review Of Ethical Topicsmentioning
confidence: 99%
“…Interventions to reduce regional differentials in health have ethical implications, as Stapleton et al (2013) showed. They used the example of placing primary care physicians to underserved areas, depending upon levels of incentive or coercion, to alleviate regional differences in primary care.…”
Section: From Theory To Interventionmentioning
confidence: 99%
“…Second, this choice also reflects systematic and introductory discussions of public health ethics. Several scholarly works also refer to the same range of principles and theories when discussing ethics in a pluralist context [11,12] but also in papers formulating ethical policy advice or being suitable directly for public health practitioners [9,[13][14][15]. Thus, our choice of approaches intends to relate to real-world discourses of public health ethics within the public health community, while referring explicitly to the most used approaches in the field.…”
Section: Methodsmentioning
confidence: 99%